2014
DOI: 10.1111/mcn.12128
|View full text |Cite
|
Sign up to set email alerts
|

Immediate or early skin‐to‐skin contact after a Caesarean section: a review of the literature

Abstract: The World Health Organization and the United Nations International Children's Emergency Fund recommends that mothers and newborns have skin-to-skin contact immediately after a vaginal birth, and as soon as the mother is alert and responsive after a Caesarean section. Skin-to-skin contact can be defined as placing a naked infant onto the bare chest of the mother. Caesarean birth is known to reduce initiation of breastfeeding, increase the length of time before the first breastfeed, reduce the incidence of exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(176 citation statements)
references
References 63 publications
(395 reference statements)
4
147
0
9
Order By: Relevance
“…For example, Weiss and colleagues (2004) observed that infants of mothers who used more stimulating touch during feeding at 3 months had better visual-motor skills and more advanced gross motor development. Other evidence has shown that skin-to-skin contact following Caesarean section may help maintain temperature of newborns and reducing new-born stress (for review, Stevens, Schmied, Burns, & Dahlen, 2014). Studies with older infants have showed that the infant's arousal can be regulated by soothing, touch-based behaviors by their caregivers, in addition to self-soothing behaviors (e.g.…”
Section: The Affectively Touched Self: Learning Bodily Pleasure and Pmentioning
confidence: 99%
“…For example, Weiss and colleagues (2004) observed that infants of mothers who used more stimulating touch during feeding at 3 months had better visual-motor skills and more advanced gross motor development. Other evidence has shown that skin-to-skin contact following Caesarean section may help maintain temperature of newborns and reducing new-born stress (for review, Stevens, Schmied, Burns, & Dahlen, 2014). Studies with older infants have showed that the infant's arousal can be regulated by soothing, touch-based behaviors by their caregivers, in addition to self-soothing behaviors (e.g.…”
Section: The Affectively Touched Self: Learning Bodily Pleasure and Pmentioning
confidence: 99%
“…27 Further evidence shows a benefit for mothers after cesarean deliveries who practice SSC as soon as the mother is alert and responsive in increased breastfeeding initiation, decreased time to the first breastfeeding, reduced formula supplementation, and increased bonding and maternal satisfaction. 28 Increasing rates of breastfeeding ultimately have short-and long-term health benefits, such as decreased risk of infections, obesity, cancer, and sudden infant death syndrome. 3 The evidence for rooming-in also extends beyond infant feeding practices and is consistent with contemporary models of familycentered care.…”
Section: Evidence For Ssc and Rooming-inmentioning
confidence: 99%
“…The World Health Organisation recommend that mothers and newborns have skin to skin as soon as the mother is alert and responsive after a caesarean section (Stevens et al 2014). A recent review was carried out to evaluate the evidence on the facilitation of skin to skin contact within one hour following delivery after a caesarean section.…”
Section: What Makes Skin To Skin Contact the Basis For Breastfeeding?mentioning
confidence: 99%
“…A recent review was carried out to evaluate the evidence on the facilitation of skin to skin contact within one hour following delivery after a caesarean section. A total of seven papers met the criteria and although evidence was limited, it did suggest that immediate contact not only increased breastfeeding initiation but also increased maternal and bonding satisfaction (Stevens et al 2014).…”
Section: What Makes Skin To Skin Contact the Basis For Breastfeeding?mentioning
confidence: 99%